Immune Checkpoint Inhibitors in Advanced Acral Melanoma: A Systematic Review - Zheng, Qingyue; Li, Jiarui; Zhang, Hanlin; Wang, Yuanzhuo; Zhang, Shu (Frontiers in Oncology, 2020)
Objective Acral melanoma (AM) has different biological characteristics from cutaneous melanoma. Although systemic therapeutic strategies for advanced AM resemble those for advanced cutaneous melanoma, the evidence of the clinical use of immune checkpoint inhibitors (ICIs) for AM is still inadequate. We aimed to systematically analyze the therapeutic effects and safety profile of ICI treatments in advanced AM. Methods This systematic review was conducted in line with a previously registered protocol. Three electronic databases, conference abstracts, clinical trial registers and reference lists of included articles were searched for eligible studies. The primary outcomes were therapeutic effects, and the secondary outcomes were the safety profiles. Results This systematic review included 6 studies investigating anti-CTLA-4 immunotherapy, 12 studies investigating anti-PD-1 immunotherapy, 1 study investigating the combination therapy of anti-CTLA-4 and anti-PD-1, and 1 study investigating anti-PD-1 immunotherapy in combination with radiation. In most studies investigating ipilimumab, the anti-CTLA-4 antibody, the objective response rate ranged from 11.4% to 25%, the median progression-free survival ranged from 2.1 months to 6.7 months, and the median overall survival was more than 7.16 months. For studies discussing anti-PD-1 immunotherapy with nivolumab, pembrolizumab, or JS001, the objective response rate ranged from 14% to 42.9%, the median progression-free survival ranged from 3.2 months to 9.2 months, and the median overall survival was more than 14 months. The combination therapy of anti-CTLA-4 and anti-PD-1 immunotherapy showed better efficacy with an objective response rate of 42.9% than single-agent therapy. The retrospective study investigating the combination therapy of anti-PD-1 immunotherapy and radiation showed no overall response. Few outcomes regarding safety were reported in the included studies. Conclusions ICIs, especially anti-CTLA-4 monoclonal antibodies combined with anti-PD-1 antibodies, are effective systematic treatments in advanced AM. However, there remains a lack of high-level proof to verify their safety and support their clinical application.